KOMBINASI ENZIM POLIGALAKTURONASE DAN ENZIM PEKTINESTERASE PADA KLARIFIKASI SARI BUAH NAGA SUPER MERAH (Hylocereus Costaricensis) DALAM PEMBUATAN SIRUP - Widowati, Esti; Sari, Ardhea Mustika; Ningsih, Rokhimah Sudarmi (Universitas Sebelas Maret (UNS), 2019)
The aim of this research was to investigated the effect of polygalacturonase enzyme (PG) from Bacillus licheniformis strain GD2a AR2 0.09%, 0.1%, and 0.11% concentration combine with pectinesterase enzyme (PE) from Bacillus licheniformis strain GD2a KK2 0.5%, 1%, and 1.5% concentration on the super red dragon fruit juice calrification in syrup production based in pH, total soluble solids, transmittance, and viscosity. Polygalacturonase enzyme hydrolized the α-1,4- D-glycosidic form galacturonic acid while the pectinesterase enzyme break the metoxyl group of pectin form pectat acid. Both PG and PE work together to hydrolized pectin. Pectinesterase catalyzed pectin become pectat acid as the substrat for polygalacturonase. In the lower acid degree, polygalcturonase and pectinesterase enzyme combination cause the viscosity and total soluble solids decrease. Degradation of pectin cause the transmittance of super red dragon fruit syrup increase. The result of this research were obtained a partially pure polygalacturonase enzyme with enzyme activity 0.31 U/ml while the pectinesterase enzyme activity was 1.167 U/ml. Samples with the addition 0.11% concentration of poligalakturonase enzyme and 0.5% concentration of pectinesterase enzyme with pH value of 4.303, total soluble solid value of 38.133oBrix, transmittance value of 74.5%T, and viscocity value of 0.128cP was selected sample.